The integration and evaluation of a social-media facilitated journal club to enhance the student learning experience of evidence-based practice: A case study - Ferguson, Caleb; DiGiacomo, Michelle; Gholizadeh, Leila; Ferguson, Leila E.; Hickman, Louise D. (Nurse education today, 2017)
Nurses are required to interpret and apply knowledge so communities will receive care based on best available evidence, as opposed to care that is simply based on tradition or authority. Fostering nursing students' critical appraisal skills will assist in their capacity to engage with, interpret and use best evidence. Journal clubs are frequently used approach to engage learners with research and develop critical appraisal skills. Given new flipped and blended approaches to teaching and learning there is need to rejuvenate how research is utilised and integrated within journal clubs to maximise engagement and translation of evidence. This paper provides a case study of a single site Australian university experience of transitioning a traditional physical journal club, to a social media-facilitated club within a postgraduate health subject to stimulate and facilitate engagement with the chosen manuscripts. This case study is based on our own experiences, supported by literature and includes qualitative comments obtained via student feedback surveys during November 2015. Case study. Social media-facilitated journal clubs offer an efficient way to continue developing critical appraisal skills in nursing students. The integration of a social media-facilitated journal clubs increased student attention, engagement with presented activities and overall student satisfaction within this evidence-based practice subject. Future rigorously-designed, large-scale studies are required to evaluate the impact of online journal clubs on the uptake of evidence-based practice, including those resulting in improved patient outcomes. •Journal clubs are frequently used approach to engage learners with research and develop critical appraisal skills.•Social media-facilitated journal clubs offer an efficient way to continue developing critical appraisal skills.•The integration of a social media-facilitated journal club increased student attention, engagement and satisfaction.